Judicial System Reform in Italy : A Key to Growth - Esposito, Gianluca; Lanau, Sergi; Pompe, Sebastiaan (Washington, D.C. : International Monetary Fund, 2014)
The inefficiency of the Italian judicial system has contributed to reduced investments, slow growth and a difficult business environment. The enforcement of civil and commercial claims suffers from excessive delays in court proceedings, resulting in a very large number of pending cases. The Italian authorities have over the years taken steps to remove bottlenecks and speed up judicial proceedings. While these measures are generally steps in the right direction, more can be done. Consideration could be given, inter alia, to reviewing court fees, improving the new mandatory mediation scheme, strengthening court management, and reforming the appeal system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Italy